Increased expression of CXCL2 in ACPA‐positive rheumatoid arthritis and its role in osteoclastogenesis. (21st October 2020) - Wang, X.; Sun, L.; He, N.; An, Z.; Yu, R.; Li, C.; Li, Y.; Li, Y.; Liu, X.; Fang, X.; Zhao, J.
Summary: Anti‐citrullinated protein/peptide antibodies (ACPA) play important roles in the pathogenesis of rheumatoid arthritis (RA). ACPA‐positive (ACPA + ) and ACPA‐negative (ACPA − ) RA were suggested to be different disease subsets, with distinct differences in genetic variation and clinical outcomes. The aims of the present study were to compare gene expression profiles in ACPA + and ACPA − RA, and to identify novel candidate gene signatures that might serve as therapeutic targets. Comprehensive transcriptome analysis of peripheral blood mononuclear cells (PBMCs) from ACPA + and ACPA − RA patients and healthy controls was performed via RNA sequencing. A validation cohort was used to further investigate differentially expressed genes via polymerase chain reaction (PCR) and enzyme‐linked immunosorbent assay (ELISA). Spearman's correlation test was used to evaluate the correlation of differentially expressed genes and the clinical and laboratory data of the patients. The role of differentially expressed genes in osteoclastogenesis was further investigated. Expression of C‐X‐C motif chemokine ligand 2 (CXCL2) was significantly increased in ACPA + RA than in ACPA − RA, which was validated in PBMCs and serum. CXCL2 promoted the migration of CD14 + monocytes and increased osteoclastogenesis in RA patients. RAW264.7 macrophages were used to investigate specific mechanisms, and the results suggested that CXCL2 stimulated osteoclastogenesis via extracellular receptor kinase (ERK) mitogen‐activated protein kinase (MAPK) and nuclear factor kappa B pathways. In conclusion, CXCL2 was highly expressed in ACPA + RA than in ACPA − RA. CXCL2 promoted osteoclastogenesis and was related to bone erosion in RA, which suggests that the blockade of CXCL2 might be a novel strategy for the treatment of RA. Abstract : CXCL2 was highly expressed in ACPA + RA than in ACPA − RA. CXCL2 promoted osteoclastogenesis and was related to bone erosion in RA, which suggest that the blockade of CXCL2 might be a novel strategy for the treatment of RA.